A Recurrent Cervical Neurenteric Cyst Treated Anteriorly: Safe, Gross-Total Excision Facilitated by Prophylactic Unilateral Vertebral Artery Exposure, Microdissection, and Spinal Cord Monitoring—A Case Report and Technical Note. (4th March 2018) - Kida, Kazunobu; Tani, Toshikazu; Kawazoe, Tateo; Hiroi, Makoto
Abstract : This study reports on a 67-year-old woman with partial Brown-Séquard syndrome due to a recurrent cervical neurenteric cyst at C3 to C4. The myelopathic symptoms reappeared 22 years after a previous shunting operation performed posteriorly with a silicone tube connecting the intradural cervical cyst cavity to the subarachnoid space. We have now succeeded in removing the cyst nearly completely with the anterior approach. The surgical procedure consisted of right vertebral artery exposure at C3 and C4 and a subtotal corpectomy of C3 followed by microdissection of the cyst, duraplasty, and iliac strut graft fusion. Spinal cord monitoring with motor-evoked potential studies helped us safely dissect the cyst wall tightly adhering to the spinal cord. Duraplasty with Gore-Tex patch-grafting in conjunction with postoperative lumbar subarachnoid drainage worked well in preventing a spinal fluid fistula. At two years after surgery, the patient showed a nearly complete return of function without any recurrence of the cyst.